2019
DOI: 10.1371/journal.pone.0214110
|View full text |Cite
|
Sign up to set email alerts
|

The Gag protein PEG10 binds to RNA and regulates trophoblast stem cell lineage specification

Abstract: Peg10 (paternally expressed gene 10) is an imprinted gene that is essential for placental development. It is thought to derive from a Ty3-gyspy LTR (long terminal repeat) retrotransposon and retains Gag and Pol-like domains. Here we show that the Gag domain of PEG10 can promote vesicle budding similar to the HIV p24 Gag protein. Expressed in a subset of mouse endocrine organs in addition to the placenta, PEG10 was identified as a substrate of the deubiquitinating enzyme USP9X. Consistent with PEG10 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 51 publications
3
55
3
Order By: Relevance
“…Our data suggest an additional function in ESC, with a new layer of regulation involving the regulation of LEFTY2 abundance, a secreted ligand that may act through cell autonomous and non-autonomous functions to regulate ESC fate. We also confirmed previous studies indicating a function of USP9X in mTOR signalling in stem/progenitor cells and its interaction with PEG proteins [51,52,63].…”
Section: Usp9x Regulates the Activity Of The Pluripotency Networksupporting
confidence: 92%
See 2 more Smart Citations
“…Our data suggest an additional function in ESC, with a new layer of regulation involving the regulation of LEFTY2 abundance, a secreted ligand that may act through cell autonomous and non-autonomous functions to regulate ESC fate. We also confirmed previous studies indicating a function of USP9X in mTOR signalling in stem/progenitor cells and its interaction with PEG proteins [51,52,63].…”
Section: Usp9x Regulates the Activity Of The Pluripotency Networksupporting
confidence: 92%
“…Co-immunoprecipitation assays followed by proteomic identified numerous proteins interacting with USP9X in ESC, and most of these interaction are disrupted by the deletion of exon 2 of Usp9X or when cells enter differentiation upon LIF removal. A recent study reported USP9X potential binding partners in ESC using a flag-tag inserted in frame in Usp9X exon 2 [63]. The study reported far less USP9X potential binding partners compared to our work, most of which are detected in the Usp9X E2/Y background.…”
Section: Usp9x Regulates Esrrb Functioncontrasting
confidence: 90%
See 1 more Smart Citation
“…PEG10-RF1/2 is, like the ancestral Gag-Pol protein, generated by a highly efficient translational frameshift between the Gag-like and Pol-like elements (Clark et al, 2007;Shigemoto et al, 2001). While in retroviruses the Pol element is subsequently cleaved from the Gag element, this proteolytic cleavage is at best weak in PEG10 (Abed et al, 2019). Instead, the "Gag-only" form PEG10-RF1 is produced when the frameshift element is bypassed and the proximal stop codon is engaged (Supplemental Figure 4C).…”
Section: Figure 2: Proteomics Of Brain and Spinal Cord Reveals Proteimentioning
confidence: 99%
“…PEG10 upregulation promotes proliferation and invasiveness of cancer cells (Akamatsu et al, 2015), and deletion in mouse models causes lethality due to placentation defects (Ono et al, 2006). Recently, it was found that PEG10 regulates mRNA abundance in murine trophoblast cells, thereby promoting their differentiation in culture (Abed et al, 2019). Furthermore, purification of PEG10-RF1 yielded virus-like particles (Abed et al, 2019), similar to the Gag-like protein ARC/ARG3.1, which binds RNAs and facilitates intercellular RNA transport among neurons (Ashley et al, 2018;Pastuzyn et al, 2018).…”
Section: Figure 2: Proteomics Of Brain and Spinal Cord Reveals Proteimentioning
confidence: 99%